PENERAPAN TEORI CONNECTIONISM DALAM PEMBELAJARAN SUSUN HURUF SISWA MI DARUSSALAM GRESIK - Umi Latifah (BASA Journal of Language & Literature, 2021)
This research is based on the background of children becoming enthusiastic about learning in various creative ways given by teachers or parents to children. Many ways and theories in learning exist to increase children's enthusiasm in the learning process, one of which is the theory of connectionism. Because it takes a stimulus to brain development in children in order to produce a response that matches the stimulus given by practicing and appreciating children's results. This article limits the problem to the application of connectionism theory with the laws in the theory, namely the law of readiness, the law of practice, and the law of effect. This research uses a qualitative approach. The design of this research is descriptive. This research data was obtained by observing the learning activities of MI Darussalam Gresik students. The population of this research is junior high school students. The data collection technique used was descriptive. Based on learning observations obtained, 1) the law of readiness of MI Darussalam Gresik students, 2) the law of practice of MI Darussalam Gresik students, and 3) the law of consequences of MI Darussalam Gresik students.